IFRS adoption and its impact on multinational entities - Kireeva, Kamilla; Procházka, David, 1979 říjen 10.-; Čiperová, Lenka; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
Implications of the IFRS transition in multinational companies – Empirical evidence from multinational companies The purpose of the future work is to study the theoretical foundations of the transition from national standards to international ones, the practice of applying several options for such a transition, consideration of the difficulties, differences and prospects for further accounting, as well as elucidating the effect of such a transition in terms of accounting indicators.
Vedoucí práce: David Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses